criticizing of the idle mind - Yadgar Lateef Gamsheer Sharazoory (پژوهشنامه ادبیات کردی, 2019)
The deeply poetic expression, the variety of views, the openness of the reader in reading to interact with him, the connection of the text with the real life are among the characteristics of fading poetry. His primary goal is to represent the world around him in poetry; he has also tried to criticize the idle and static mind and avoid it. Despite being a religious poet, he is not only unaware of the reality of life, but also with his enlightened spirit and exalted spirit has sought to use real life in various aspects and to show his appreciation for life. Let. The study consists of three topics: The first section is devoted to key concepts such as the unemployed mind and the concept of interpretation; The third section, devoted to the discussion of the horizon of waiting and the horizon of movement, consists of two sub-categories: textual deviation and the aesthetic perspectives of the poet.